2019
DOI: 10.1021/acs.orglett.8b03847
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Bond Insertion Triggers Highly Regioselective 1,4-Aminomethylamination of 1,3-Enynes with Aminals Enabled by Pd-Catalyzed C–N Bond Activation

Abstract: A highly chemo- and regioselective 1,4-aminomethylamination of simple enynes with aminals to allenic 1,5-diamines by taking advantage of C–N bond activation has been reported. The reaction proceeds under mild reaction conditions and can be performed under lower catalyst loading (0.1 mol %) with high efficiency and broad substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…On the base of the previous studies [ 13‐14,21‐29 ] and our experimental results, a plausible mechanism for this α‐aminomethylation is proposed (Figure 1). Firstly, the aza‐Michael addition reaction takes place between the aminal 1a and the nitrodiene 2a to form the key intermediate I .…”
Section: Resultssupporting
confidence: 70%
“…On the base of the previous studies [ 13‐14,21‐29 ] and our experimental results, a plausible mechanism for this α‐aminomethylation is proposed (Figure 1). Firstly, the aza‐Michael addition reaction takes place between the aminal 1a and the nitrodiene 2a to form the key intermediate I .…”
Section: Resultssupporting
confidence: 70%
“…In the initial stage of designing the synthetic routes of the tetrahydroisoquinoline compound, we found that an interesting structure of bis(tetrahydroisoquinoline) acetal amine (Figure 3) was discussed as one useful intermediate. 8 A further thorough literature survey showed that acetal amines were mainly used for aminomethylation reactions, 9 and to our knowledge, there is no relevant study about the use of methylene as a protecting group in the field of metalation reactions by organic lithium etc. We considered that the acetal amine unit could have good compatibility in the presence of strong bases such as organic lithium at low temperatures and could be applied to the synthesis of tetrahydroisoquinoline-6carboxylic acid 1 as a protecting group.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…All reagents were obtained from commercial suppliers and used without further purification. All cobalt catalysts were prepared according to the literature., 1,3-Enynes were prepared according to the previously reported method . The 1 H, 13 C, 19 F, and 31 P NMR spectra were recorded on a Bruker Avance 400 or 600 spectrometer.…”
Section: Experimental Sectionmentioning
confidence: 99%